2019
DOI: 10.1080/02665433.2019.1570475
|View full text |Cite
|
Sign up to set email alerts
|

From Geddes’ city museum to Farrell’s urban room: past, present, and future at the Newcastle City Futures exhibition

Abstract: Genuine engagement about how best to achieve liveable urban futures should be part of planning's raison-d'etre but it has a chequered history of delivery. Exhibitions harnessing the communicative power of mixed media and linked to a progressive and responsive programme of focused discussion and debate remain relevant to community consultation and civic engagement. Terry Farrell's concept of the 'urban room' to involve citizens in engaging with the past, present, and future of towns and cities offers a contempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…There are only a few studies that have been conducted around urban planning exhibitions worldwide, concerning their historical development (Freestone, 2015;Freestone & Amati, 2011;Hein, 2015;Nakajima, 2021;Tewdwr-Jones et al, 2020), exhibition design (Tan & Cho, 2022;Lu et al, 2020;Qian & Wu, 2012), and its connected political metaphors (de Jong et al, 2018). So far, there is a gap in research on the effects of urban planning exhibitions on the communication of planning contents.…”
Section: Jones Et Al 2020)mentioning
confidence: 99%
See 2 more Smart Citations
“…There are only a few studies that have been conducted around urban planning exhibitions worldwide, concerning their historical development (Freestone, 2015;Freestone & Amati, 2011;Hein, 2015;Nakajima, 2021;Tewdwr-Jones et al, 2020), exhibition design (Tan & Cho, 2022;Lu et al, 2020;Qian & Wu, 2012), and its connected political metaphors (de Jong et al, 2018). So far, there is a gap in research on the effects of urban planning exhibitions on the communication of planning contents.…”
Section: Jones Et Al 2020)mentioning
confidence: 99%
“…For example, through post-visit ratings and interviews Fan (2014) found that visitors were generally content with its role of communication while there are limited opportunities for public participation. Tewdwr-Jones et al (2020) demonstrated that the visitor interaction board, which was used at the Newcastle City Futures exhibition, received predominantly positive feedback from visitors. Nakajima (2021) compared the post-visit ratings of experts and non-experts for each program presented at the 'Urbanism Places Exhibition 2018' in Shinjuku, Japan.…”
Section: Jones Et Al 2020)mentioning
confidence: 99%
See 1 more Smart Citation
“…The work included developing both a trust-building exercise through visual means (Tewdwr-Jones et al, 2019) and a state of the region report (Tewdwr-Jones et al, 2015) that would be used in the later period of NCF's endeavour. This was an attempt to get partners across sectors to work together to think of new shared project ideas.…”
Section: Newcastle City Futures: a Quadruple-helix Urban Platformmentioning
confidence: 99%
“…But it would be necessary for this visualisation to become part of the broader metropolitan planning process, where professionals listen and view a citizen's perspective of the urban together with their likes and dislikes, represented in visual form. Pilot exercises run in Newcastle upon Tyne indicate a positive take-up of new digital photographic, video and drawing media in addressing the long-term future of the city, often led by children and young people that, in turn, attract the attention of parents, grandparents and other family members and friends (Tewdwr-Jones et al, 2019). The challenge would be to convince professional planners to see the knowledge gathering, idea generating merits of more visual means that could inform their hitherto closed and predominantly written communication devices.…”
Section: Spatial Imaginariesmentioning
confidence: 99%